2005
DOI: 10.1074/jbc.m413673200
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of Epidermal Growth Factor Receptor (EGFR) Signaling and Enhanced Activation of Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL) Receptor-mediated Apoptosis Induction by an scFv:sTRAIL Fusion Protein with Specificity for Human EGFR

Abstract: Epidermal growth factor receptor (EGFR) signaling inhibition by monoclonal antibodies and EGFR-specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 51 publications
2
67
0
1
Order By: Relevance
“…22,23 We already reported that ad-TRAIL could overcome TRAIL resistance in several TRAIL-resistant cell lines. 14 Recently, tumor-cell selective modification of soluble TRAIL by fusing epidermal growth factor receptordirected antibody (scFv425) showed a more selective and potent antitumor effect, 24 and a recombinant adenovirus that can express fusion protein (scFv425-TRAIL) demonstrated its clinical significance. 25 However, resistance to TRAIL prevents its clinical use and requires the combination with other chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 We already reported that ad-TRAIL could overcome TRAIL resistance in several TRAIL-resistant cell lines. 14 Recently, tumor-cell selective modification of soluble TRAIL by fusing epidermal growth factor receptordirected antibody (scFv425) showed a more selective and potent antitumor effect, 24 and a recombinant adenovirus that can express fusion protein (scFv425-TRAIL) demonstrated its clinical significance. 25 However, resistance to TRAIL prevents its clinical use and requires the combination with other chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other anti-EGFR scFv-TRAIL fusion proteins showed rapid inactivation of the EGFR signaling pathways in various other tumor cell lines (e.g., A431; ref. 26). In our study, we applied a humanized version of clinically approved antibody cetuximab for the generation of the antibody-scTRAIL fusion proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Positive controls included a glioblastoma tumour sample expressing both the wild-type EGFR (wtEGFR) and EGFRvIII, and a cell line transfected with an EGFRvIII plasmid (Jurkat.EGFRvIII; Bremer et al, 2005).…”
Section: Rt -Pcr For Egfrviiimentioning
confidence: 99%